Association between pre-pregnancy body weight and dietary pattern with large-for-gestational-age infants in gestational diabetes - Ana Munda; Marjanca Starčič Erjavec; Katja Molan; Jerneja Ambrožič Avguštin; Darja Žgur-Bertok; Draženka Pongrac Barlovič (Diabetology & Metabolic Syndrome, 2019)
Abstract Background Both obesity and gestational diabetes (GDM) are associated with adverse outcomes. Diet during pregnancy impacts weight gain and fetal growth. Therefore, we aimed to explore non-pharmacological treatment success depending on pre-pregnancy body weight and its association with large for gestational age (LGA) infants in women with GDM. Methods In our observational study we investigated 57 singleton pregnant women with GDM. All women received standard treatment, including healthy diet education and regular medical checkups. Data were collected through blood analysis, medical records and questionnaires assessing diet before conception and during pregnancy. Differences in dietary patterns were compared in normal weight and overweight/obese group using Mann–Whitney U, Wilcoxon Signed Rank Test or Kruskal–Wallis test, as appropriate. Logistic regression was used for prediction of LGA. p-value less than 0.05 was used for statistical significance. Results Preconceptionally, the Mann–Whitney U test showed that the normal-weight group (n = 41) more frequently consumed fruits (U = 116.5, p < 0.001), eggs (U = 189.5, p = 0.02), cheese (U = 148.0, p = 0.003) compared to the overweight/obese group (n = 16), that consumed more beef (U = 407.0, p = 0.03) and low-calorie beverages (U = 397.0, p = 0.05). During pregnancy both groups improved their diet, with no differences detected. Personality types differed only preconceptionally with regard to healthy diet. Excessive gestational weight gain did not significantly differ between body-weight groups (16.6% vs. 23.1%), neither did the incidence of LGA infants (46.2% vs. 43.8%). Significant predictors of LGA were paternal height (OR = 1.12, 95% CI 1.01–1.23), 3rd trimester HbA1c (OR = 0.50, 95% CI 0.26–0.97), unemployment (OR = 4.80, 95% CI 1.12–20.61) and diet improvement during pregnancy (OR = 1.19, 95% CI 1.02–1.39). After adjustment improvement in diet was no longer a significant predictor for LGA. Conclusion Even though dietary patterns of the participants significantly improved during pregnancy, LGA infants were born independently of pre-pregnancy weight or diet and despite good glycemic control. Further research is needed to explore social determinants of health and whether solutions outside the health sector could provide efficient means in preventing adverse pregnancy outcomes as well as improving metabolic health.